Plan de exportación de panela orgánica desde Colombia a Francia (2021)
In this document a compilation of literature is made as a methodology for the development of an organic panela export plan from Colombia to France, it was necessary to recognize the panela market within the countries of the European Union and carry out a documentary review to understand and determine the economic and financial viability of the project. This project is not directed by any specific company, the idea is to propose an export model that is capable of accommodating the needs of any company that wishes to export panela to France. Initially, a market study is carried out in the city of Bordeaux in France, since it has one of the most important maritime ports in the country and it is determined that its population density is in accordance with the objectives to be achieved in terms of marketing of panela. Therefore, an economic study was carried out where export costs and expenses are identified.